Redesigning Vina@QNLM for Ultra-Large-Scale Molecular Docking and Screening on a Sunway Supercomputer - Lu, Hao; Wei, Zhiqiang; Wang, Cunji; Guo, Jingjing; Zhou, Yuandong; Wang, Zhuoya; Liu, Hao (Frontiers in Chemistry, 2021)
Ultra-large-scale molecular docking can improve the accuracy of lead compounds in drug discovery. In this study, we developed a molecular docking software, Vina@QNLM, which can use more than 480,000 parallel processes to search for potential lead compounds from hundreds of millions of compounds. We proposed a task scheduling mechanism for large-scale parallelism based on Vinardo and Sunway’s new-generation supercomputer architecture. Then, we re-adopted the core docking algorithm to incorporate the full advantage of the heterogeneous multicore processor architecture in intensive computing. We successfully expanded it to 104,650,651 cores (161,001 management process elements and 10,304,064 computing process elements), with a strong scalability of 55.92%. To the best of our knowledge, this is the first time that 10 million cores are used for molecular docking on Sunway. The introduction of the heterogeneous multicore processor architecture achieved the best speedup that is 11x than that of the management process element of Sunway. The performance of Vina@QNLM was comprehensively evaluated using the CASF2013 and CASF-2016 protein–ligand benchmarks, and the screening power was the highest out of the 27 software tested in the CASF-2013 benchmark. In some existing applications, we used Vina@QNLM to dock more than 10 million molecules to nine rigid proteins related to SARS-CoV-2 within 8.5 hours on 10 million cores. We also developed a platform for the general public to use the software.